Locus of control among individuals with different pain conditions - Bonafé, Fernanda Salloumé Sampaio (2019)
The objective of this study was to evaluate the psychometric properties of the Multidimensional Health Locus of Control - Form C (MHLC-C) scale applied to a sample of adult Brazilian patients with different pain conditions. The scores were then identified and compared on each of the subscales and profiles regarding locus of control. The sample consisted of 1,149 adult individuals (79% women; mean age: 36.6 years) of which 334 reported not feeling pain in the prior 24 hours, 386 reported pain in the prior three months, 250 reported recurring pain for the prior three months or longer, and 179 reported continuous pain for the prior three months or longer. A confirmatory factor analysis was performed. The invariance of the MHLC-C was tested on independent samples. The weighted global score was calculated for each of the factors and tested using ANOVA (α = 5%). Individuals were classified according to the eight health locus of control (HLC) profiles. The factors fit the data adequately after the model was refined. A higher score for the Health Professionals HLC was found among individuals reporting less than three months of pain. The "believer in control" profile was the most prevalent among the groups, while the least prevalent profile was the "pure chance" profile. The MHLC-C was found to be valid and reliable for assessing locus of control among people with different pain conditions. Only the Health Professionals HLC factor exhibited significantly different results for these individuals. The "believer in control" profile was the most prevalent among the pain conditions considered.